Planning forest recreation in natural protected areas of southern Durango, Mexico - Pérez Verdín, Gustavo; Lee, Martha E.; Chavez, Deborah J. (Instituto de Ecología, A.C., 2016)
This research investigated the usefulness of the Recreation Opportunity Spectrum (ROS) for managing forest recreation in two natural protected areas of southern Durango, Mexico. We used onsite interviews to document the recreation activities visitors participated in, the characteristics of their preferred recreation sites, and socio-demographic information. A cluster analysis identified visitor groups based on the characteristics of preferred recreation sites and the resulting clusters were compared to the recreation activities and socio-demographic data to create a typology of visitors. We used the ROS framework to identify three classes in each natural protected area including (1) zones with easy access and basic facilities (ROS rural class), (2) natural-appearing zones with few facilities (ROS roaded class), and (3) reserve zones (ROS semiprimitive non-motorized or primitive class). Overall, the ROS framework appears to fit appropriately in these two case studies and could be used for recreation planning purposes in other forest areas of the country.